Impact of neuraminidase inhibitors on influenza A(H1N1)pdm09-related pneumonia: an IPD meta-analysis. - Muthuri,SG; Venkatesan,S; Myles,PR; Leonardi-Bee,J; Lim,WS; Mamun,AA; Anovadiya,AP; Araújo,WN; Azziz-Baumgartner,E; Báez,C; Bantar,C; Barhoush,MM; et al. (Influenza and Other Respiratory Viruses, 2015)
BACKGROUND: The impact of neuraminidase inhibitors (NAIs) on Influenza-related pneumonia (IRP) is not established. Our objective was to investigate the association between NAI treatment and IRP incidence and outcomes in patients hospitalised with A(H1N1)pdm09 virus infection. METHODS: A worldwide meta-analysis of individual participant data (IPD) from 20,634 hospitalised patients with laboratory confirmed A(H1N1)pdm09 (n=20,021) or clinically diagnosed (n=613) 'pandemic influenza'. The primary outcome was radiologically confirmed influenza-related pneumonia (IRP). Odds ratios (OR) were estimated using generalized linear mixed modelling, adjusting for NAI treatment propensity, antibiotics and corticosteroids. RESULTS: Among 20,634 included participants, 5,978 (29.0%) had IRP; conversely, 3,349 (16.2%) had confirmed absence of radiographic pneumonia (the comparator). Early NAI treatment (within 2 days of symptom onset) versus no NAI was not significantly associated with IRP [adj. OR 0.83 (95%CI 0.64 - 1.06; p=0.136)]. Among the 5,978 patients with IRP, early NAI treatment versus none did not impact on mortality [adj. OR=0.72 (0.44-1.17; p=0.180)] or likelihood of requiring ventilatory support [adj. OR=1.17 (0.71-1.92; p=0.537)]; but early treatment versus later significantly reduced mortality [adj. OR=0.70 (0.55-0.88; p=0.003)] and likelihood of requiring ventilatory support [adj. OR=0.68 (0.54-0.85; p=0.001)]. CONCLUSIONS: Early NAI treatment of patients hospitalised with A(H1N1)pdm09 virus infection versus no treatment did not reduce the likelihood of IRP. However, in patients who developed IRP early NAI treatment versus later reduced the likelihood of mortality and needing ventilatory support. This article is protected by copyright. All rights reserved.